Soft tissue sarcoma: DWI and DCE-MRI parameters correlate with Ki-67 labeling index. - Lee, Ji Hyun; Yoon, Young Cheol; Seo, Sung Wook; Choi, Yoon-La; Kim, Hyun Su (European Radiology, 2020)
Objectives: To examine the correlation of diffusion-weighted and dynamic contrast-enhanced magnetic resonance imaging (MRI) parameters with Ki-67 labeling index (LI) in soft tissue sarcoma (STS).Methods: The institutional review board approved this retrospective study, and the requirement for informed consent was waived. Thirty-six patients with STS who underwent 3.0-T MRI, including diffusion-weighted and dynamic contrast-enhanced MRI, between July 2011 and February 2018, were included in this study. The mean and minimum apparent diffusion coefficients (ADCs) (ADCmean and ADCmin, respectively), volume transfer constant, reflux rate, and volume fraction of the extravascular extracellular matrix of each lesion were independently analyzed by two readers. Their relationship with the Ki-67 LI was examined using Spearman's correlation analyses. Differences between low- and high-proliferation groups based on Ki-67 LI were evaluated statistically. Optimal cut-off points were determined using the area under the curve analysis for significant parameters. Interobserver agreement was assessed with the intraclass correlation coefficient.Results: ADCmean (ρ = - 0.333, p = 0.047) was significantly and inversely correlated with Ki-67 LI. The high-proliferation group showed a significantly lower ADCmean than did the low-proliferation group (median, 1.08 vs. 1.20; p = 0.048). When a cut-off ADCmean value of 1.16 × 10-3 mm2/s was used, the sensitivity, specificity, and area under the curve for differentiating low- and high-proliferation groups were 75.0%, 60.0%, and 0.712, respectively. Interobserver agreements between the two readers were almost perfect for all parameters.Conclusions: ADCmean was correlated with Ki-67 LI and could help differentiate between STS with low and high proliferation potential.Key Points: • ADC meanwas significantly and inversely correlated with Ki-67 labeling index in soft tissue sarcoma. • In the high-proliferation group, ADC meanvalues were significantly lower than those of the low-proliferation group.